Identifying 3000-Year Old Human Interaction Spheres in Central Fiji through Lapita Ceramic Sand-Temper Analyses - Roselyn Kumar; Patrick D. Nunn; Elia Nakoro (Geosciences, 2021)
Petrographic analyses of sand tempers in Pacific Island potsherds reveal information about ancient human interactions within archipelagic contexts. By comparison with bedrock mineralogy, analyses of 45 sherds from the Lapita settlement at Naitabale on Moturiki Island (central Fiji) show that most sherds were manufactured locally but that a minority is exotic. Using ternary plots of LF-QF-FM (LF—lithic fragments; QF—quartz + feldspar; FM—ferromagnesian), it is shown that exotic material (either pots or temper sands) most likely came from elsewhere in Fiji, probably southeast Viti Levu Island, central Lau, Lomaiviti and Kadavu. Geoscientific analyses of archaeological samples therefore gives us insights into how people likely interacted within the Fiji Archipelago three millennia ago.